Prospective assessment of the predictive value of the BRCA1 gene status in sarcoma patients treated with trabectedin: an updated analysis of the EORTC 62091 trial. (15th April 2018) - Italiano, Antoine; Touati, Nathan; Litière, Saskia; Collin, Françoise; Pourquier, Philippe; Gronchi, Alessandro
Abstract : We describe the predictive value of BRCA1 gene status on trabectedin efficacy and found no correlation despite the mechanisms of action of this drug that rely on DNA repair systems.